Counter Unmanned Aircraft Systems Technologies and Operations - Nichols, Randall K.; Mumm, Hans C.; Lonstein, Wayne D.; Ryan, Julie J.C.H; Carter, Candice (Open textbook library., 2024)
As the quarter-century mark in the 21st Century nears, new aviation-related equipment has come to the forefront, both to help us and to haunt us. (Coutu, 2020). This is particularly the case with unmanned aerial vehicles (UAVs). These vehicles have grown in popularity and accessible to everyone. Of different shapes and sizes, they are widely available for purchase at relatively low prices. They have moved from the backyard recreation status to important tools for the military, intelligence agencies, and corporate organizations. New practical applications such as military equipment and weaponry are announced on a regular basis – globally. (Coutu, 2020). Every country seems to be announcing steps forward in this bludgeoning field.